Pengaruh Pajak Daerah, Retribusi Daerah, Hasil Pengelolaan Kekayaan Daerah yang Dipisahkan dan Lain-Lain Pendapatan Asli Daerah yangb Sah Terhadap Pendapatan Asli Daerah Kab. Deli Serdang - Jihan Afiyah; Emi Masyitah (Journal on Education, 2023)
This research was motivated by the Original Income of the Deli Serdang Regency for the last 10 years, only able to achieve the target in 2017. This type of research is Associative research. The population in this study is the Recapitulation Report of the Regional Budget of Deli Serdang Regency for the 2013-2022 Period which is accessed through the Djpk.kemenkeu.go.id website. The sample in this study used census sampling. The data used are secondary data with literature study techniques and documentation studies. This study used quantitative analysis methods. Data analysis techniques are Descriptive Statistical Analysis Test, Classical Assumption Test and Hypothesis Test. The results and discussion of this study show that Regional Taxes and Other Legal Local Original Revenues have a significant and positive partial effect, while Regional Levies do not have a partial effect that is not significant and positive and The results of the management of the separated regional wealth do not have a partial effect that is not significant and negative on the original income of the Deli Serdang District. However, Regional Taxes, Regional Levies, Results of Segregated Regional Wealth Management and Other Legal Local Original Revenues have a simultaneous effect on the Local Original Revenue of Deli Serdang District.